Anodontophorus n. nov., a new name for Anodontophora Pomorski, 2007, not Anodontophora Cossmann, 1897 - Pomorski, Romuald J. (Zootaxa, 2007)
I recently proposed the generic name of Anodontophora for a new onychiurid species Anodontophora tuvensis Pomorski, 2007 (Collembola, Onychiuridae) (Pomorski, 2007). However, this name is a junior homonym of Anodontophora Cossmann, 1897, used as genus name for extinct, fossil mussels, (Mollusca: Bivalvia: Unionida) (Cossmann, 1897). According to the principle of homonymy the name Anodontophora Pomorski 2007 is not applicable (ICZN, 1999), and therefore I propose here the name Anodontophorus n. nov. (gender masculine) with type species Anodontophorus tuvensis (Pomorski, 2007).